Analisis Pengaruh Alokasi Dana Desa, Program Keluarga Harapan, dan Program Indonesia Pintar dalam Penanggulangan Kemiskinan (Studi pada Kecamatan-Kecamatan di Kabupaten Wonogiri Tahun 2018-2020) - Febriani, Lisa Tri; Arif, Muhammad (Universitas Muhammadiyah Surakarta, 2023)
This study aims to determine magnitude of the influence of the government's program Allocation of Village Funds (ADD), the Family Hope Program (PKH), and the Smart Indonesia Program (PIP) in poverty alleviation in Wonogiri Regency in 2018-2020. The data used is panel data. The analytical tool used is panel data regression analysis with the best estimation model Fixed Effect Model (FEM). The results showed that the Village Fund Allocation (ADD) had a negative effect on the percentage of poverty. Meanwhile, the Family Hope Program (PKH) and the Smart Indonesia Program (PIP) have no effect on the Poverty Percentage. The government is expected to increase its role in poverty alleviation in Wonogiri Regency. For example, by improving data collection so that the program is right on target.